Memorandum on first steps towards the improvement of the general medical services of the nation (London : Council of the Medical Practioners' Union, 1939)
1939 1939 1930s 6 pages ORDERED TO BE PRINTED BY THE COUNCIL OF THE MEDICAL PRACTITIONERS' UNION AT ITS MEETING ON 11th JANUARY, 1939. ALFRED WELPLY, Secretary. 56, Russell Square, W.C.1. 36/H24/38